Fabrication of lecithin-gum tragacanth muco-adhesive hybrid nano-carrier system for in-vivo performance of Amphotericin B. (15th August 2018) - Jabri, Tooba; Imran, Muhammad; Shafiullah,; Rao, Komal; Ali, Imdad; Arfan, Muhammad; Shah, Muhammad Raza
Graphical abstract: Highlights: Amphotericin B was loaded in lecithin nanoparticles. Gum tragacanth gold nanoparticles were synthesized. Lecithin-gum tragacanth muco-adhesive hybrid nano-carrier system was developed. Amphotericin B oral bioavailability was investigated. Abstract: Nano-carriers are excellent systems for improving bioavailability of poor aqueous soluble drugs. This study focuses fabrication of lecithin-gum tragacanth muco-adhesive hybrid NPs for enhancing Amphotericin B (AmpB) oral bioavailability. AmpB loaded lecithin NPs were synthesized through solvent diffusion method. Green synthesis of stable muco-adhesive gum tragacanth (GT) gold NPs was confirmed through UV–vis spectrophotometer and FT-IR. AmpB loaded lecithin NPs hybrid with GT gold NPs were characterized for shape, size, polydispersity index (PDI), zeta potential, drug entrapment efficiency and drug-excepients interactions using atomic force microscope (AFM), zetasizer, UV–vis spectrophotometer and FT-IR respectively. In-vivo bioavailability of AmpB loaded in NPs was investigated in rabbits. AmpB loaded muco-adhesive NPs were found polydispersed with 358.3 ± 1.78 nm mean size and −19.9 ± 0.51 mV zeta potential. They entrapped 78.91 ± 2.44% AmpB and enhanced its oral bioavailability in animals. Results reveal the hybrid NPs as efficient carriers for enhancing AmpB oral bioavailability in controlled manner.